LIFE QUALITY OF YOUNG MEMBERS OF A OBESITY MULTIPROFESSIONAL PROGRAM (Fiep Bulletin - online, 2012)
Excess weight has affected an increasing number of individuals and an increasingly earlyage, producing as a reflex inumerous negative effects on life quality (QOL). The aim of this study was to evaluate the effects of the Multidisciplinary Treatment of Obesity Program (PMTO) on the life quality of teenagers. The study included 21 teenagers who underwent 16 weeks in PTMO during 2010. To evaluate the QOL instrument was usedPedsQL 4.0, which has six dimensions, physical, emotional, social, educational, psychosocial and total. The cutoff points proposed by Cole et al. were used as reference to characterize obesity in groups. We applied Shapiro-Wilk test to verify the normality of data distribution and applied the Student t test and Wilcoxon test when comparing the preand post  intervention, we also calculated the percentage difference between the pre and post intervention by the formula (final value-baseline value inicial/100 *). We adopted a significance level of 5%. The results showed significant improvement in weight and BMI after 16 weeks. We also observed significant differences between the two moments in relation to the dimensions: emotional (p0.004), social (p0.040), psychosocial (p 0.010) and total (p 0.006). It is concluded that the approach and threatment constituted an importantt reatment strategy for obese adolescents, enabling improved overall QOL.